2012
DOI: 10.2308/accr-10218
|View full text |Cite
|
Sign up to set email alerts
|

Nonfinancial Disclosure and Analyst Forecast Accuracy: International Evidence on Corporate Social Responsibility Disclosure

Abstract: We examine the relationship between disclosure of nonfinancial information and analyst forecast accuracy using firm-level data from 31 countries. We use the issuance of stand-alone corporate social responsibility (CSR) reports to proxy for disclosure of nonfinancial information. We find that the issuance of stand-alone CSR reports is associated with lower analyst forecast error. This relationship is stronger in countries that are more stakeholder-oriented—i.e., in countries where CSR performance is more likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

60
1,023
3
21

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,369 publications
(1,235 citation statements)
references
References 63 publications
60
1,023
3
21
Order By: Relevance
“…Empirical evidence also links CSR disclosure with positive economic outcomes, such as reduced cost of equity capital (Dhaliwal et al 2011), and increased analyst forecast accuracy (Dhaliwal et al 2012). However, the prior research does not consistently report a positive relationship between CSR and economic outcomes.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Empirical evidence also links CSR disclosure with positive economic outcomes, such as reduced cost of equity capital (Dhaliwal et al 2011), and increased analyst forecast accuracy (Dhaliwal et al 2012). However, the prior research does not consistently report a positive relationship between CSR and economic outcomes.…”
Section: Introductionmentioning
confidence: 91%
“…Simnett et al 2009, Dhaliwal et al 2012). The results of these studies could potentially be driven by a few outlier country-level measures.…”
Section: Diversity Of Countries Included In Multi-country Csr Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the number of companies issuing stand-alone CSR reports has increased dramatically (Dhaliwal, Radhakrishnan, Tsang, & Yang, 2012), in most jurisdictions CSR reporting is not mandatory (some exceptions include France, Denmark and Sweden) (Tschopp & Nastanski, 2014). In the EU, this is currently changing with the directive on disclosure of non-financial and diversity information.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these analysts achieve lower analyst forecast errors and dispersion" (p. 59). Dhaliwal, et al (2012) reported that "the issuance of stand-alone CSR reports is associated with lower analyst forecast error" (p. 723). There was no detailed examination of the contents of CSR reports in either of these studies; rather, CSR reporting was operationalized as just the presence or absence of a report.…”
Section: Empirical: Correlates Of Csr Reportingmentioning
confidence: 99%